Macular ischaemia: a contraindication for anti-VEGF treatment in retinal vascular disease?. Issue 2 (16th January 2012) - Manousaridis, Kleanthis; Talks, James
Abstract : Anti-vascular endothelial growth factor (anti-VEGF) therapy has been shown to be effective at improving vision in patients with macular oedema due to diabetic retinopathy and vein occlusions, but blocking VEGF at least in theory could be detrimental to vascular integrity. For this reason, some patients with macular ischaemia were excluded from studies showing the effectiveness of therapy. A considerable number of patients present with mixed pathology of macular oedema and macular ischaemia and it is often impossible to determine the degree to which ischaemia accounts for decreased vision. In this review, the authors have dealt with the specific question of whether or not there is evidence to support potential worsening of the macular perfusion and visual function after anti-VEGF treatment with bevacizumab or ranibizumab for macular oedema secondary to diabetic retinopathy or retinal vein occlusions, especially if there is coexisting macular ischaemia. The authors conclude that anti-VEGF therapy rarely seems to further compromise the retinal circulation; however, worsening of macular ischaemia in the long term cannot be definitely excluded, particularly in eyes with significant ischaemia at baseline and after repeated intraocular anti-VEGF injections. The decision to offer prolonged anti-VEGF treatment in cases of significant coexisting macular ischaemia should not be based only on measurements of macular thickness; instead repeat fluorescein angiograms should be performed.